Aspectos ecológicos da tripanossomíase americana: XIV - Persistência e potencial de domiciliação de populações triatomínicas silvestres em região de intensa atividade agropecuária Ecological aspects of South American tripanosomiasis: XIV - Persistence and domiciliation potential of sylvatic triatominae populations in an intensive agricultural and cattle breeding region - Oswaldo Paulo Forattini; Octávio Alves Ferreira; Eduardo Olavo da Rocha e Silva; Ernesto Xavier Rabello (Universidade de São Paulo, 1979)
São apresentados os resultados de observações sobre populações triatomínicas extradomiciliares em região de intensa atividade agropecuária. Os restos de vegetação primitiva, embora reduzidos a menos de 8,0%, mostraram-se suficientes para manter essas populações. Pelo menos para Triatoma sordida, a destruição progressiva parece favorecer sua sobrevivência, graças à multiplicação de ecótopos preferidos por esse triatomíneo. Tanto essa espécie como Panstrongylus megistus e Rhodnius neglectus mostraram-se aptos à colonização em ecótopos artificiais representados por galinheiros experimentais. The results of observation of sylvatic triatominae population in a region of intensive agricultural and cattle breeding activity are reported. Important environmental changes had occurred in the area, including destruction of the primitive vegetation and intensive use of pesticides. Nevertheless, these modifications apparently did not affect the survival of Triatominae, since they were found in the remaining vegetation. Moreover, this destruction seems to have favored, to some extent, survival of Triatoma sordida by increasing the available ecotopes. This species, as well as Panstrongylus megistus and Rhodnius neglectus, showed enough ecological valence to colonize experimental fowes houses, used as artificial ecotopes.